How to solve this exponential equation:7*3^x+1-5^x+2=3^x+4-5^x+3

The answer is supposed to be x=-1 but I'm not getting that.

### 1 Answer | Add Yours

7*3^x+1-5^x+2=3^x+4-5^x+3

=> (7*3)3^x - 25*5^x = 81*3^x - 125*5^x

Taking everything to one side

=> (21-81) * 3 ^x +(-25+125)* 5 ^x = 0

=>100* 5 ^x = 60* 3 ^x

=> 5 * 5 ^x = 3* 3^x

=> 5^(x+1) = 3^(x +1)

taking log of both the sides

=> (x+1) log 5 = (x+1) log 3

But log 5 is not equal to log 3

Therefore x+1= 0

Therefore x=-1 ... Answer

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes